الخصائص السلوكية للتلاميذ المتفوقين كما يدركها أساتذة التعليم الابتدائي لمدينة الأغواط - زنبط مباركة; عديلة نعيمة; بوفاتح محمد (My University, 2019)
The present study aimed at revealing the behavioral characteristics of the outstanding pupils in the primary education stage (from the point of view of the teachers) within the schools of the city of Laghouat ،The questionnaire was distributed behavioral characteristics, Prepared by the researcher Osama Maeijini (1997),The study was based on descriptive methodology. Where the questionnaire was distributed to the teachers to identify behavioral characteristics of pupils who excel academically from their point of view and is a questionnaire of behavioral characteristics whose characteristics were confirmed by a random sample of 20 individuals ،and then apply, the tool mentioned in the final image on a sample intended 60 teachers and professors. After the results are sorted with the ( spss) program, we get the following results: - There are multiple behavioral characteristics of outstanding pupils. - There are differences between the teachers in assessing the behavioral characteristics of pupils attributed to gender. - There are differences between teachers in assessing the behavioral characteristics of pupils attributed to seniority. Academic excellence _Behavioral characteristics_ the pupils _Primary education teachers.